Georg Forster’s Activities at Vilnius University - Genzelis, Bronislovas (Problemos, 1973)
Georg Forster, the famous West European thinker, traveller and revolutionary, headed the Chair of the History of Natural Sciences from 1784 to 1787 at the Chief Lithuanian School (Vilnius University). In his lectures and articles of that time he developed the theory of man’s natural origin; he explained natural phenomena from the materialistic point of view. Forster based his cognition theory on the principles of sensualism. He defended his views in his polemics with Immanuel Kant on the origin of human races. While in Vilnius, Forster critisized sharply the feudal system and propagated the theory of the natural law. An attempt is being made in the present paper to determine Forster’s ideological influence upon the enlightenment movement in Lithuania.